Failure in syndromic management due to drug-resistant Mycoplasma genitalium in Florianópolis, South Brazil - Hartmann Barazzetti, Fernando; Schörner, Marcos André; Ribeiro, Jhonatan Augusto; Grisard, Henrique Borges da Silva; Martins, Jéssica Motta; Wachter, Julia Kinetz; Vanny, Patrícia de Almeida; Bazzo, Maria Luiza (Brazilian Journal of Sexually Transmitted Diseases, 2024)
Introduction: Mycoplasma genitalium is a bacterium associated with sexually transmitted infections that can cause urethritis in men and complications in women, including preterm birth. Increasing macrolide resistance in M. genitalium poses challenges to treatment efficacy. Objective: To present a case of treatment failure of urethritis caused by macrolide-resistant M. genitalium. Case report: This case report describes a 20-year-old man with persistent urethral symptoms despite azithromycin treatment, wherein M. genitalium harbored the A2058G mutation in the 23S rRNA. Subsequent treatment with moxifloxacin resolved symptoms and cleared M. genitalium. Conclusion: The study highlights the importance of resistance testing to guide antimicrobial therapy and emphasizes the need for updated treatment guidelines in Brazil.